Implementation of Law Enforcement and Disciplinary Policies in the Instruction of the Minister of Home Affairs No. 15 of 2021 in Banten - Supriyadi, Agus; Alamsah, Nandang; Nurasa, Heru; Pancasilawan, Ramadhan (KnE Social Sciences, 2022)
This research investigated the implementation of the law enforcement and disciplinary policies of the Governor’s Instruction number 15 of 2021, focusing on the province of Banten, where during the pandemic period, law enforcement and discipline experienced many obstacles. George C. Edward’s policy implementation theory was used, which examines four variables that affect the success of policy implementation, namely communication, resources, disposition, and bureaucratic structure. A qualitative research method was used and data were collected through literature studies, observations and interviews. Triangulation techniques were used. The results demonstrated that the central government’s policy regarding emergency PPKM was only able to reduce in small quantities according to the target, due to the many inhibiting factors. The authors conclude that it may be time to focus on herd immunity, and that we must understand that to solve this problem we need to increase antibodies or community immunity, so the policies issued must lead to increasing these factors. The research also focused on helical trauma and the implementation of psychological treatment. Keywords: policy implementation, law enforcement, COVID-19, PPKM